Implementasi Metode Weighted Aggregated Sum Product Assessment (WASPAS) Dalam Penentuan Kayu Terbaik Untuk Bahan Gitar - Simanjuntak, Paulus; Irma, Irma; Mesran, Mesran (STMIK Budi Darma, 2018)
Decision Support System is a computer program used by decision makers such as in determining the best wood for guitar material based on predetermined criteria of assessment through the design of decision support systems that are expected to produce useful information with a fairly accurate efesiansi in the process of determining wood. Thus, it can be proposed the development of operational system of guitar timber determination by using the application of timber selection decision support system for guitar. So as to create an ease in the process of determining timber on producers and consumers. In this study used WASPAS method, so the results obtained are expected to help facilitate the process of determining the best wood for guitar making materials.